AI Adoption in Product Innovation: How Artificial Intelligence Helps Create More Relevant Products? - Azzaakiyyah, Hizbul Khootimah; Suherlan; Pramono, Susatyo Adhi (PT. LITERASI SAINS NUSANTARA, 2025)
The adoption of artificial intelligence (AI) in product innovation has become a key factor in creating products that are more relevant to customer needs. AI enables companies to analyze market trends, optimize product design, and personalize offerings based on consumer preferences. This study is a literature review employing a qualitative approach and descriptive analysis, utilizing data from Google Scholar and credible websites from 2018 to 2025. From an initial 30 articles, a rigorous selection process reduced the sample to 18 primary sources for this research. The findings indicate that AI has had a significant impact across various industries, such as automotive, healthcare, retail, and food, by enhancing innovation efficiency and aligning products more precisely with customer needs. However, AI adoption in product innovation also faces challenges, including data quality, algorithmic bias, and difficulties in integrating technology at the organizational level. The implications of this research highlight the importance of optimizing AI strategies in product development, improving human resource competencies, and establishing regulations that support ethical and sustainable AI implementation. Therefore, companies need to develop more adaptive strategies for integrating AI to create more competitive product innovations that align with market dynamics.